The Priming Effects of Mirror Visual Feedback on Bilateral Task Practice: A Randomized Controlled Study - Yi-chun Li; Ching-yi Wu; Yu-wei Hsieh; Keh-chung Lin; Grace Yao; Chia-ling Chen; Ya-Yun Lee (Hindawi-Wiley, 2019)
The priming effect of mirror visual feedback can be simply provided by inexpensive mirror therapy (MT), which exhibits beneficial effects on sensorimotor recovery in stroke. The present study was a single-blind pretest-posttest study that examined whether the priming effect of mirror visual feedback on bilateral task practice would render better outcomes. Twenty-three patients with chronic stroke were randomized to receive hospital-based task-oriented MT or bilateral arm training (BAT) for 4 weeks at 90 minutes/day, 3 days/week and a home practice for 30-40 minutes/day, 5 days/week. There was the potential trend for MT to improve temperature sense as measured by the revised Nottingham Sensory Assessment (Cohen's d=1.00; 95% confidence interval, -0.09 to 2.09), and MT increased the Stroke Impact Scale 3.0 total score (d=0.89; 0.003 to 1.71). MT also showed a trend for greater improvements in the Motor Activity Log (amount of use: d=0.62; -0.24 to 1.44; quality of movement: d=0.50; -0.35 to 1.31). MT involving bilateral movement practice with the priming effect of mirror visual feedback may render beneficial effects. The unilateral approach or MT augmented by extra feedback might be appropriate modifications.